The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/anie.201900099
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Role of Hyaluronic Acid in Trafficking siRNA Across the Cellular Barrier: The First Biomimetic, Anionic, Non‐Viral Transfection Method

Abstract: Circulating nucleic acids,s uch as short interfering RNA( siRNA), regulate many biological processes;h owever, the mechanism by whichthese molecules enter the cell is poorly understood. The role of extracellular-matrix-derived polymers in binding siRNAs and trafficking them across the plasma membrane is reported. Thermal melting, dynamic light scattering, scanning electron microscopy, and computational analysis indicate that hyaluronic acid can stabilizesiRNAvia hydrogen bonding and Vand er Waals interactions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
(15 reference statements)
1
29
0
Order By: Relevance
“…They also demonstrated that the presence of salt was needed to minimize the ionic repulsion between HA and siRNA. By taking these considerations into account, they achieved a 55% gene silencing efficiency in vitro with the optimized HA:siRNA ratio [130].…”
Section: Hyaluronic Acid For Sirna Deliverymentioning
confidence: 99%
“…They also demonstrated that the presence of salt was needed to minimize the ionic repulsion between HA and siRNA. By taking these considerations into account, they achieved a 55% gene silencing efficiency in vitro with the optimized HA:siRNA ratio [130].…”
Section: Hyaluronic Acid For Sirna Deliverymentioning
confidence: 99%
“…As a result, B16F10 and 4T1cells highly expressed CD44, accounting for approximately 73.2% and 91.5%, respectively, while A549 cells showed extremely lower CD44 expression with a mere 8.5% (supplementary Figure S1). The HA based active targeting nanomedicines have been a research hotspot in the field of cancer therapy duo to the enhanced targeting efficacy and improved antineoplastic activities (Lv et al, 2018;Paidikondala et al, 2019;Phua et al, 2019). 4T1, B16F10 and A549 cells were chosen for this research and we have figured out B16F10 cells were highly expressed CD44 proteins, while A549 cells showed low expression of CD44 proteins, which were exploited for the biological evaluation of a redox-sensitive hyaluronic acidbased nanomedicine…”
Section: Cellular Uptake and Location Of C6-labeled Ha-ss-tos Micellementioning
confidence: 99%
“…10 We have recently developed the first non-cationic nonviral siRNA delivery method using hyaluronic acid, a natural biopolymer present in the extracellular matrix. 11 In this communication, we present synthesis of a novel 4 0 -guanidinium modified siRNA and its systematic physicochemical, biochemical, computational and in vitro gene silencing analysis. The GMU modification at the 3 0 -end is expected to be protonated under physiological conditions, 12,13 which could enhance nuclease stability, [14][15][16] and potentially improve immunocompatibility.…”
mentioning
confidence: 99%